2016
DOI: 10.1177/230949901602400121
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Cervical, Thoracic, and Lumbopelvic Sagittal Alignment in Healthy Adults

Abstract: Purpose. To evaluate the association between cervical sagittal alignment and thoracic/lumbopelvic sagittal alignment in healthy Japanese adults. Methods. 30 male and 22 female healthy adults aged 22 to 50 years were recruited. Spinal parameters were measured on radiographs, including the cervical sagittal vertical axis, sagittal vertical axis, C7 tilt angle, Ishihara index for cervical lordosis, thoracic kyphosis, lumbar lordosis, sacral slope, pelvic tilt, and pelvic incidence. Results. The C7 tilt angle posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Some studies have reported a difference between sexes in kyphosis and lordosis angle, showing a higher angle of kyphosis in males and a higher angle of lordosis in females [54,55]. However, others have found differences just in kyphosis [56] or just in lordosis [57]. Only one study researched the effect of the exercise on kyphosis angle differences between sexes, finding the same result in both sexes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a difference between sexes in kyphosis and lordosis angle, showing a higher angle of kyphosis in males and a higher angle of lordosis in females [54,55]. However, others have found differences just in kyphosis [56] or just in lordosis [57]. Only one study researched the effect of the exercise on kyphosis angle differences between sexes, finding the same result in both sexes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Such changes with age may put pressure on cervical spine to change simultaneously causing changes such as increase in lordosis seen by some authors. Whereas in healthy adults (aged 22–50 years), cervical sagittal alignment is found to be associated with thoracic sagittal alignment but not with lumbopelvic alignment [ 49 ] and cervical lordosis inversely correlates with thoracic kyphosis [ 50 ]; in elderly people, cervical curvature is affected by pelvic sagittal alignment [ 51 ]. Lumbar lordosis decreases, and thoracic kyphosis increases with age which results in a compensatory increase in cervical lordosis [ 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the C2-C7 angle is well correlated with T1S and global thoracic curvature in the up-right neutral position. 3,4 The present study demonstrated that cervical sagittal motion affects the T1S and T5-T8 angle, but the T1-T4 angle, T9-T12 angle, and lumbo-pelvic columns did not change significantly. The reciprocal change of T1-T4 angle was smaller than that of T5-T8 angle upon cervical flexion and extension.…”
Section: Discussionmentioning
confidence: 43%